Intersectionality, Inc.: A Dialogue on Intersectionality’s Travels and Tribulations - Grzanka, Patrick R.; Bhatia, Rajani; Lewis, Mel Michelle; Parks, Sheri L.; Woodfork, Joshua C.; Casiano, Michael (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
In a roundtable discussion held at the American Studies Association’s annual meeting in 2013, the authors interrogate intersectionality’s uptake in diverse settings, considering how its radical potential may be coopted and conflated with “diversity,” “multiculturalism,” “inclusion,” and similarly neoliberal institutional imperatives. The authors also discuss opportunities for resistance and transformation.